2010
DOI: 10.1103/physrevb.82.054423
|View full text |Cite
|
Sign up to set email alerts
|

Interplay betweenCo3dandCe4fmagnetism in CeCoAsO

Abstract: We have investigated the ground-state properties of polycrystalline CeCoAsO by means of magnetization, specific heat, and solid-state NMR. Susceptibility and specific-heat measurements suggest a ferromagnetic order at about, T C = 75 K. No further transitions are found down to 0.5 K. At 6.5 K a complex Schottky type of anomaly shows up in the specific-heat results. The interplay between Ce 4f and Co 3d magnetism being responsible for that anomaly is discussed. Furthermore 75 As-NMR investigations have been per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 35 publications
4
37
0
Order By: Relevance
“…According to µ eff = (µ 1/2 , we can estimate the effective moment of Co, which gives µ Co =1.2 µ B , being consistent with that reported in Ref. 26.…”
Section: Gdfe1−ycoyasosupporting
confidence: 91%
See 1 more Smart Citation
“…According to µ eff = (µ 1/2 , we can estimate the effective moment of Co, which gives µ Co =1.2 µ B , being consistent with that reported in Ref. 26.…”
Section: Gdfe1−ycoyasosupporting
confidence: 91%
“…[23][24][25] Moreover, the Co-end compounds, namely ReCoP nO, demonstrate rich magnetic properties attributed to the interactions between the 3d and 4f electrons. For example, CeCoAsO and CeCoPO exhibit an enhanced Sommerfeld coefficient of 200 mJ/mol-K 2 , and their Co-ions undergo a FM transition at T Co C = 75 K. 26,27 LaCoAsO and LaCoPO are itinerant ferromagnets with a Curie temperature of T Co C = 50 K and 60 K, respectively. 28 Complex magnetic properties were observed in SmCoAsO and NdCoAsO, in which the Co-ions first undergo a FM transition and then an AFM transition upon cooling from room temperature, 29,30 followed by an AFM transition of the 4f electrons at T Sm N = 5 K and T Nd N = 3.5 K. 29,30 In GdCoAsO, both Co and Gd are magnetically ordered too, 31 but there is no systematic study so far.…”
Section: K)mentioning
confidence: 99%
“…Previous first principles calculation on LaT AsO [21] suggested that Fe and Co ions show SDW-like and FM instabilities at low temperatures respectively, while Ni ions display nonmagnetic behavior. For CeT AsO, Fe ions in CeFeAsO indeed show SDW-like AFM instability and Co ions in CeCoAsO are FM ordered [14,15], meanwhile neither local magnetic moment nor long range magnetic order of Ni ions is observed in CeNiAsO. However, this does not mean that the Kondo coupling between Ce moment and conduction carriers in the NiAs layer is weaker than that in the FeAs layer.…”
Section: +mentioning
confidence: 90%
“…By comparison, CeOsPO shows the Ce 3+ AFM order at 4.5 K while CeRuPO is a rare example of the FM Kondo lattice with T C = 15 K [12]. For the case of T = Co, both CeCoPO and CeCoAsO show the FM correlated Co-3d magnetism [13,14,15].…”
Section: Introductionmentioning
confidence: 97%
“…16,17 On the Co-rich side, the ferromagnetically ordered Co ions have a strong polarization effect on the AFM order of Ce moments. 14,18 On the other hand, in the Gd(Fe,Co)AsO series, which correspond to the case of a large 4f -magnetic moment, Fe/Co substitution also leads to a superconducting dome near the 3d-electron magnetic instability. 14 On the Co-rich side, in contrast to the Ce-case, the large moment of Gd ions is robust against the FM order of Co moments, and maintains its AFM order with a nearly unchanged Néel temperature over the entire doping range.…”
Section: Introductionmentioning
confidence: 99%